Das Dionysosmosaik in Virunum. Entdeckung, Besitz und Restaurierung - GLASER, Franz; PÖSCHL, Günther
The Dionysus Mosaic of Virunum was discovered in 1898 in the insula to the West of the forum; today it is displayed in the Kärntner Landesmuseum in Klagenfurt. The Roman building comprised 19 rooms with mosaic floors; some of them had been destroyed since the Middle Ages. The Dionysus Mosaic comes from a 33 m² big dining room and is nearly wholly preserved. The central panel is decorated with a hexagonal composition with Dionysus, the Menads, four peacocks and small birds. G. Hellenkemper-Salies dated the mosaic around 230/40 AD. The article mainly deals with the history of the acquisition of the mosaic.
p. 327-341, 4 ill. n.b.Éditeur : Graz, Phoibos
Keywords: Bibliographie par pays, région ou ensemble géographique; Dionysos; Forum (Klagenfurt, AUT); Hexagone; Histoire des collections; Maison (Klagenfurt, AUT) de Dionysos; Ménade; Musée (Klagenfurt, AUT) Kärntner Landesmuseum; Oiseau; Panneau; Paon; Salle d’apparat; Klagenfurt